Oral bovine colostrum supplementation enhances buffer capacity but not rowing performance in elite female rowers - Brinkworth, G. D.; Buckley, J. D.; Bourdon, P. C.; Gulbin, J. P.; David, A. Z. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
A randomized, double-blind, placebo controlled design was used in which 13 elite female rowers, all of whom had competed at World Championships, were supplemented with 60 g day-1 of either bovine colostrum (BC; n = 6) or concentrated whey protein powder (WP; n = 7) during 9 weeks of pre-competition training. All subjects undertook the study as a group and completed the same training program. Prior to, and after 9 weeks of supplementation and training, subjects completed an incremental rowing test (ROW1) on a rowing ergometer consisting of 3 3 4-min submaximal workloads and a 4-min maximal effort (4max), each separated by a 1-min recovery period. The rowing test was repeated after a 15-min period of passive recovery (ROW2). The 4max for ROW1 provided a measure of performance, and the difference between the 4max efforts of ROW1 and ROW2 provided an index of recovery. Blood lactate concentrations and pH measured prior to exercise and at the end of each workload were used to estimate blood buffer capacity (b). Food intake was recorded daily for dietary analysis. There were no differences in macronutrient intakes (p > .56) or training volumes (p > .99) between BC and WP during the study period. Rowing performance (distance rowed and work done) during 4max of ROW2 was less than ROW1 at baseline (p < .05) but not different between groups (p > .05). Performance increased in both rows by Week 9 (p < .001), with no difference between groups (p > .75). However, the increase was greatest in ROW2 (p < .05), such that by Week 9 there was no longer a difference in performance between the two rows in either group (p > .05). b was not different between groups for ROW1 at baseline (BC 38.3 ± 5.0, WP 38.2 ± 7.2 slykes; p > .05) but was higher in BC by Week 9 (BC 40.8 ± 5.9, WP 33.4 ± 5.3 slykes; p < .05). b for ROW2 followed the same pattern of change as for ROW1. We conclude that supplementation with BC improves b, but not performance, in elite female rowers. It was not possible to determine whether b had any effect on recovery.